2020
DOI: 10.3897/neobiota.60.55366
|View full text |Cite
|
Sign up to set email alerts
|

Multi-taxa inventory of naturalized species in Chile

Abstract: Here we present a multi-taxa inventory of naturalized alien species recorded on continental Chile and adjacent marine habitats, including eight taxonomic groups. We identified 1,122 species. These comprise 790 vascular plants (terrestrial and aquatic); 31 nonvascular plants [Bryophyta (mosses), Marchantiophyta (liverworts) and Anthocerotophyta (hornworts)]; 18 marine and freshwater macro and micro algae; 71 fungi; 39 terrestrial vertebrates (amphibians, reptiles, mammals and birds); 108 insects; 37 marine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
0
10
0
16
Order By: Relevance
“…Basidiomata infected by Sepedonium were collected during opportunistic forays in temperate central Chile in the administrative regions of Biobío, Ñuble and Araucanía (Figure 1, Table S1), approximately between 36 habitats are supporting a unique combination of autochthonous and adventitious Boletales [22][23][24][25], many of them compatible with mycophilic Sepedonium spp., conditions which allowed us a broad approach towards novel knowledge of diversity, distribution and specificity patterns of the mycoparasite and its hosts in a relatively small geographic area.…”
Section: Study Area and Materials Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basidiomata infected by Sepedonium were collected during opportunistic forays in temperate central Chile in the administrative regions of Biobío, Ñuble and Araucanía (Figure 1, Table S1), approximately between 36 habitats are supporting a unique combination of autochthonous and adventitious Boletales [22][23][24][25], many of them compatible with mycophilic Sepedonium spp., conditions which allowed us a broad approach towards novel knowledge of diversity, distribution and specificity patterns of the mycoparasite and its hosts in a relatively small geographic area.…”
Section: Study Area and Materials Collectionmentioning
confidence: 99%
“…Looking at these rather complex nutrient pathways towards Sepedonium in forest ecosystems, it is of importance to estimate the invasive potential of allochthonous parasitehost associations in endemic communities, especially in a mosaic landscape consisting of exotic timber plantations and native forest remnants which characterizes not only our study area in central Chile, but nowadays exists globally in many regions [25,43,47]. Amanita muscaria accompanied by Chalciporus piperatus was originally adventitious with introduced Monterrey Pine in Southern Chile, but is now observed in pure Nothofagus forest with increasing frequency [24,25]; it can therefore safely be assumed that a host-tree switch has taken place from Pinus to Nothofagus which has the capacity to promote penetration of Amanita into native forest as a precursor or vector, as well for Chalciporus as for exotic Sepedonium spp., where competition with, or even replacement of, endemic fungi on both, mycorrhizal and mycoparasitic level may occur. Time will reveal whether resilience of the endemic taxa is strong enough to integrate this co-invasive force in a stable community, without erosion or even loss of native fungal diversity.…”
Section: Trophic Connections and Specificity Within Parasite-host Guilds: Invasive Vs Endemic Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…La nomenclatura y origen geográfico de las especies sigue a Rodríguez et al (2018). A cada especie se le asignó una forma de vida de Raunkiaer (1934) y la distribución geográfica original según Fuentes et al (2020). Se recolectaron y herborizaron plantas de la mayor parte de las especies.…”
Section: Métodos De Floraunclassified
“…A search of specimens of the species was conducted in the SGO herbarium, as well as a revision of background information about the presence of the species in Chile through consultation of different checklists (e.g., Zuloaga et al 2008, Ugarte et al 2011, Morales 2018, Rodríguez et al 2018, Fuentes et al 2020. Within that research, a collection of the species dated from year 1960 was found (SGO 130347) which has not been previously identified.…”
mentioning
confidence: 99%